Redox polymers for rechargeable metal-ion batteries. Issue 2 (May 2020) - Chen, Yuan; Zhuo, Shuming; Li, Zengyu; Wang, Chengliang
Highlights: Redox polymers for batteries and their charge storage mechanisms are overviewed. The applications of redox polymers in metal-ion batteries are thoroughly summarized. Redox polymers are promising for batteries with intercalation of large-sized ions. Conjugated porous polymers are outstanding for intercalation of large-sized ions. Abstract: Redox polymers have the advantages of potentially low-cost, flexibility, sustainability, high redox activity, good electrochemical reversibility and high energy density, which have been widely reported in energy storage devices. Their electrochemical properties can be easily tailored by molecular engineering. Herein, the polymers including conducting polymers, organosulfur polymers, radical polymers, carbonyl polymers, polymers of arylamines, polymers based on unsaturated C-N and C-C bonds are overviewed and their applications in various metal-ion (Li +, Na +, K +, Zn 2+, Mg 2+, Ca 2+, Al 3+ ) batteries are comprehensively summarized. By virtue of the advantage of molecular design, conjugated porous polymers are specifically highlighted due to the further enhancement of ionic diffusion and accommodation of inserted ions, which combine the merits of flexibility of organic/polymeric materials and the advantages of porous structures. In the last section, strategies for improving electrochemical properties of metal-ion batteries are discussed, followed by the prospects of key challenges and future trends of redox polymers as electrode materials for advanced electrochemical energy storage devices. Graphical abstract: Image, graphical abstract